2001
DOI: 10.1038/35083506
|View full text |Cite
|
Sign up to set email alerts
|

A giant stream of metal-rich stars in the halo of the galaxy M31

Abstract: The Milky Way is a cannibal. Recent observations have revealed the detritus of its digestion of the Sagittarius Dwarf and Magellanic Clouds, apparent as streams of gaseous and stellar debris littering the Galactic Halo ? , ? , ? . The analysis of this material has shown that the dark matter distribution within our own Galaxy is nearly spherical ? , and that much of the Galactic Halo is made up of cannibalized satellite galaxies ? , ? . Yet it remains unclear whether such halo substructures really are as ubiqui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
645
3

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 543 publications
(678 citation statements)
references
References 27 publications
28
645
3
Order By: Relevance
“…This work has revealed the Giant Southern Stream (Ibata et al 2001), a halo substructure connecting with other filagree noted around the M31 disk (e.g., Ibata et al 2004, Fardal et al 2006Gilbert et al 2007, which makes it a "Sgr stream-equivalent" in our spiral twin sister. Other M31 halo substructure has also been revealed (e.g., Chapman et al 2008) as well as an entire host of newly found M31 dSph satellites (e.g., Martin et al 2006 S. R. Majewski et al 2007, Zucker et al 2007, Irwin et al 2008, McConnachie et al 2008.…”
Section: Deep Pointed Surveys Of Nearby Galaxies Part IImentioning
confidence: 99%
“…This work has revealed the Giant Southern Stream (Ibata et al 2001), a halo substructure connecting with other filagree noted around the M31 disk (e.g., Ibata et al 2004, Fardal et al 2006Gilbert et al 2007, which makes it a "Sgr stream-equivalent" in our spiral twin sister. Other M31 halo substructure has also been revealed (e.g., Chapman et al 2008) as well as an entire host of newly found M31 dSph satellites (e.g., Martin et al 2006 S. R. Majewski et al 2007, Zucker et al 2007, Irwin et al 2008, McConnachie et al 2008.…”
Section: Deep Pointed Surveys Of Nearby Galaxies Part IImentioning
confidence: 99%
“…The faint structures visible by eye in Figure 1 have effective V-band surface brightnesses in the range 29-30 magnitudes per square arcsec. Early versions of our M31 maps have been discussed in Ibata et al (2001), Ferguson et al (2002) and Irwin et al (2005).…”
Section: The Int Wfc Surveys Of M31 and M33mentioning
confidence: 99%
“…Figure 1 shows the distribution of "blue" RGB stars across our survey area. As already apparent from our interim results [8,4], the distribution of giant branch stars at large radius is very far from uniform. Many of the clumpy features visible in the stellar distribution have effective surface brightnesses Σ V ∼ > 28 mag sq.…”
Section: Introductionmentioning
confidence: 53%
“…deg. (163 contiguous pointings) around M31 with 800-1200 sec exposures in the V and i passbands [8,4,10]. This depth is sufficient to reach V∼ 24.5, i∼ 23.5, and hence probe the top three magnitudes of the red giant branch (RGB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation